(untitled) (American Journal of Islam and Society, 2006)
Zvi Ben-Dor Benite has contributed an important piece to the history of Muslims in imperial China, centered on a seventeenth-century Muslim genealogy known as the Jing Xue Xi Chuan Pu (hereinafter Genealogy), which has been recently discovered, punctuated, and printed as the Jing Xue Xi Chuan Pu (Xining: Qinghai Renmin Chubanshe, 1989). His book follows Sachiko Murata’s study of Confucian Muslim texts and teachers (namely, Chinese Gleams of Sufi Light: Wang Tai-Yu’s Great Learning of Pure and Real and Liu Chih’s Displaying the Concealment of the Real Realm [Albany, NY: State University of New York, 2000]) and illuminates many aspects of the Muslims’ cultural life in imperial China. The book consists of an introduction, four chapters, and a conclusion with tables and illustrations. The first chapter decodes the Genealogy and outlines the trajectory of the Chinese Muslims’ educational network in central and coastal China. The second chapter explores the “social logic” behind the practices of the Muslim literati (p. 74) – that is, how they envisioned and understood the educational system, their roles, and Islam in reference to imperial China’s existing sociocultural categories. This chapter reveals how Muslim educational institutions enabled and empowered Muslim intellectuals to convert “Islam” and “Muslim” into valid social categories of school (xuepai) and to envision themselves as “literati” (shi) that were as much Chinese as Muslim. The third chapter analyzes the transformation of Islamic knowledge from “orality” to “texuality” (p. 158) and the formation of the Chinese Islamic school, which was patterned on contemporary Chinese schools of scholarship. The fourth chapter explains how Confucian Muslims interpreted Islam, Prophet Muhammad, and Islamic canons as equivalents and counterparts of Confucianism (enumerated in the Han Kitab as “Dao,” “Sage,” and “Classic”), and how the Muslim literati embraced Confucianism. In the ...